2016
DOI: 10.1080/02770903.2016.1188942
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and subjective sleep disordered breathing in a large cohort of urban adolescents

Abstract: Objective Sleep disordered breathing (SDB) has not been well studied in urban adolescents with asthma in community settings. Nor has the association of SDB symptoms and asthma severity been studied. We characterized self-reported symptoms suggesting SDB and investigated the association of SDB symptoms, probable asthma, and asthma severity. Methods 9,565 adolescents from 21 inner-city high schools were screened for an asthma intervention study. Students reported on symptoms suggesting SDB using questions from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…However, children aged 12-14 years old always sleep alone and parents cannot observe their sleep conditions very well which may affect SDB prevalence. Among other demographic correlates, we did not identify an association between SDB symptoms and gender, correlating with the findings of a previous study [2]. An association between SDB symptoms and BMI was also not identified in this study.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, children aged 12-14 years old always sleep alone and parents cannot observe their sleep conditions very well which may affect SDB prevalence. Among other demographic correlates, we did not identify an association between SDB symptoms and gender, correlating with the findings of a previous study [2]. An association between SDB symptoms and BMI was also not identified in this study.…”
Section: Discussionsupporting
confidence: 76%
“…Sleep quality is critical for the growth and development of children [1]. Sleep-disordered breathing (SDB) is a syndrome common in childhood, the spectrum of which ranges from primary snoring to partial or complete airway obstruction, termed obstructive sleep apnea syndrome (OSAS) [2]. It is important to determine the prevalence of SDB in children because of its association with the functioning of various organs, including immune responses, cardiovascular function, and neurocognitive function [2].…”
Section: Introductionmentioning
confidence: 99%
“…SRBD are common in childhood; its spectrum ranges from primary snoring to partial or complete airway obstruction, which is termed obstructive sleep apnea syndrome (OSAS) [ 6 ]. SRBD affects 5.1–13.3% of children [ 7 16 ], resulting in dysfunction of immune responses, cardiovascular function, and neurocognitive function [ 6 ]. Recently, research has shown that asthma is associated with a high risk of SRBD in children.…”
Section: Introductionmentioning
confidence: 99%
“…Another meta-analysis of 12 studies that included 38,766 subjects showed that SRBD is correlated with the prevalence of asthma in children (OR, 1.58; 95% CI, 1.35–1.80) [ 14 ]. Zandieh et al enrolled 9,565 adolescents in their study and found that adolescents with asthma have 2.63 times higher odds of developing SRBD than those without asthma [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…studied asthma and SRBD in 9565 adolescents and found that adolescents with probable asthma had 2.63 higher odds of reporting SRBD symptoms. [ 20 ] There is a lack of data in India on population-based studies in asthma and SRBD.…”
Section: Discussionmentioning
confidence: 99%